2004
DOI: 10.1128/aem.70.8.4800-4806.2004
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Different Hypervariable Regions ofrrsGenes for Use in Fingerprinting of Microbial Communities by PCR-Denaturing Gradient Gel Electrophoresis

Abstract: Denaturing gradient gel electrophoresis (DGGE) has become a widely used tool to examine microbial diversity and community structure, but no systematic comparison has been made of the DGGE profiles obtained when different hypervariable (V) regions are amplified from the same community DNA samples. We report here a study to make such comparisons and establish a preferred choice of V region(s) to examine by DGGE, when community DNA extracted from samples of digesta is used. When the members of the phylogeneticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
300
0
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 429 publications
(316 citation statements)
references
References 41 publications
6
300
0
8
Order By: Relevance
“…The first PCR was carried out using 27F (Lane, 1991) and 1401R (Nübel et al, 1996) primers, while for the second PCR, 27F-GC and 519R (Turner et al, 1999) primers were applied (which resulted in 16S rRNA gene amplicons containing the V1-V3 variable regions to get high resolution DGGE patterns; Yu and Morrison, 2004;Youssef et al, 2009) Bacterial community profiles were revealed and compared by DGGE using 7% (w/v) polyacrylamide gel containing a 40 to 60% gradient of denaturants (100% is defined as 40% formamide and 7 M urea). The electrophoresis was carried out at 60 °C in 1× Tris-acetate-EDTA (TAE) buffer at 120 V for 14.5 hours using a phorU-2 electrophoresis system (Ingeny International, Goes, Netherlands).…”
Section: Denaturing Gradient Gel Electrophoresis (Dgge)mentioning
confidence: 99%
“…The first PCR was carried out using 27F (Lane, 1991) and 1401R (Nübel et al, 1996) primers, while for the second PCR, 27F-GC and 519R (Turner et al, 1999) primers were applied (which resulted in 16S rRNA gene amplicons containing the V1-V3 variable regions to get high resolution DGGE patterns; Yu and Morrison, 2004;Youssef et al, 2009) Bacterial community profiles were revealed and compared by DGGE using 7% (w/v) polyacrylamide gel containing a 40 to 60% gradient of denaturants (100% is defined as 40% formamide and 7 M urea). The electrophoresis was carried out at 60 °C in 1× Tris-acetate-EDTA (TAE) buffer at 120 V for 14.5 hours using a phorU-2 electrophoresis system (Ingeny International, Goes, Netherlands).…”
Section: Denaturing Gradient Gel Electrophoresis (Dgge)mentioning
confidence: 99%
“…Subsamples of extracted DNA were kept at −20°C for further quantitative and qualitative analysis. Bacterial 16S rRNA genes suitable for diversity profiling of denaturing gradient gel electrophoresis (DGGE) were amplified using primer sets 954f-GC/1369r (Yu and Morrison 2004). Detailed thermal profiles of PCR amplification have been described in previous studies (Yu and Morrison 2004).…”
Section: Soil Microbial Activity Measurementsmentioning
confidence: 99%
“…Bacterial 16S rRNA genes suitable for diversity profiling of denaturing gradient gel electrophoresis (DGGE) were amplified using primer sets 954f-GC/1369r (Yu and Morrison 2004). Detailed thermal profiles of PCR amplification have been described in previous studies (Yu and Morrison 2004). Briefly, a touchdown thermal cycle strategy consisting of 10 cycles (30 s at 94°C, annealing for 30 s at temperature decreased from 61 to 56°C and extension at 72°C for 1 min) followed the additional 22 cycles (consisting of 30 s at 94°C, 30 s at 56°C, 1 min at 72°C) and then a final extension for 5 min at 72°C were performed.…”
Section: Soil Microbial Activity Measurementsmentioning
confidence: 99%
“…Therefore, we approached the analysis of the structure and dynamics of the eubacterial community by combining DGGE with SSCP. The V3 region of the 16S rRNA gene was selected to enhance the range of DGGE resolution (63), while longer DNA fragments encompassing the V4 to V5 region were generated to improve the phylogenetic inference through SSCP analysis.…”
Section: Discussionmentioning
confidence: 99%